Media literacy and digital citizenship: Student self-perceptions in a Peruvian university - Turpo Gebera, Osbaldo (2025)
The relationship between Media Literacy (ML) and Digital Citizenship (DC) is fundamental, as critical media understanding directly promotes ethical participation in digital environments. This study examines this interaction among students at a public university in Peru, using a quantitative, cross-sectional design with an analytical, correlational, and explanatory approach, based on a sample of 906 participants. The results revealed a positive and significant correlation between ML and DC (β=0.477, p<0.001), of moderate intensity, indicating the influence of factors such as the digital divide. No significant differences were found by gender, but a slight disadvantage in DC for women was observed, highlighting the need for inclusive strategies. Additionally, it was identified that dimensions of ML, such as critical media evaluation, have a significant impact on DC, emphasizing the importance of adjusting curricular content.